Math bilang - Callanta, Ma. Irene I.; del Castillo, Marion S.; Gaerlan, Ma. Joan; Molato, Maricris M.; Palomique, Norleen O. (2001)
Several systems for gesture recognition have been developed using different strategies and approaches. This paper describes a system for real time gesture recognition, which can distinguish a small vocabulary of about 14 different, static hand gestures. The fourteen gestures are representatives for actions of Addition, Multiplication, Division, Subtraction and the numbers One to Ten. A voice translation of the mathematical expression and its corresponding answer is also part of this system. Our approach uses two-dimensional images of hand postures. The pattern recognition is employed using the back propagation algorithm. All the computation occurs on a SGI workstation. Experiments with our system achieved recognition accuracy up to 90%. Our system uses input from a monocular color video camera.